Kemampuan Literasi Anak: Bagaimana Peran Serta Orang Tua di Masa Pandemi Covid-19? - Deliana Sari; Jelita Jelita (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2021)
Literacy skills in children include the ability to hear, read, write, and speak. Increasingliteracy skills in children can develop children's thinking patterns to be more critical and logical insolving problems, express new ideas, and be able to understand what information is obtained frombooks, audios, and other sources. However, currently, Covid-19 has appeared across the world,resulting in many institutions closing, including educational institutions, to break the chain of Covid-19 spread. The purpose of this study was to analyze how the role of parents in improving literacy skillsin children, especially during the pandemic. One of the guardians of grade one at MIS Paya BujokTunong, Langsa City became the subject of research using this type of qualitative research through anaturalistic approach that is descriptive and interview techniques as a research instrument. Theresults of this study indicate that parents' awareness and ways of improving literacy skills in childrenare very important to capture interest and disinterest in children. In addition, during this pandemic,the learning process is also carried out at home, thus a friendly way using soft intonation can maintainthe mood. children in the process of improving literacy skills in children.